Development of an LC-MS method for the determination of simvastatin and its hydroxy acid form in muscle tissue and method application - Ewa Paszkowska; Karolina Pietrowska; Steen Larsen; Emilia Fornal; Michał Ciborowski (PLoS ONE, 2025)
Purpose Statins are the most commonly used drugs worldwide. Besides a significant decrease in cardiovascular diseases (CVDs) risk, the use of statins is also connected with a broad beneficial pleiotropic effect. At the same time, it is burdened with different side effects. The most common ones are muscle issues (from mild myalgia to rhabdomyolysis). The mechanisms of many of them are still unclear. Therefore, an analytical method for the determination of simvastatin (SIM) and its main metabolite (the hydroxy acid form – SIMA) in muscle tissue was developed. Methods Muscle samples were homogenized with ammonium acetate buffer using the bead mill homogenizer, and then statins were extracted with a mixture of methanol and ethanol. Prepared samples were analyzed with liquid chromatography (using a reverse-phase column with a gradient elution) combined with the mass spectrometer which was operated in a multiple reaction monitoring mode. Results The assay was linear over a 0.1–5 ng/mL range for both statin forms. Inter- and intra-day precision and accuracy were characterized. The method was considered precise (with the following relative standard deviation values: 6.0–6.9% for SIM, and 8.1–12.9% for SIMA) and accurate (with the following mean accuracies: 91.4–100.1% for SIM, and 102.2–115.4% for SIMA). The extraction efficiency was evaluated by recovery determination (76% for SIM, and 99% for SIMA). Moreover, the matrix effect was calculated with the following results: 87% for SIM, and 139% for SIMA. The proposed method was applied for SIM and SIMA determination in skeletal muscle tissues obtained from statin-treated patients. Conclusion The obtained results proved that the method may be a useful tool for explaining muscle effects related to statin therapy.